Hard iron boride (Fe2B) on 99.97wt% pure iron - Ozdemir, Ozkan; Usta, Metin; Bindal, Cuma; Ucisik, A. Hikmet (Pergamon-Elsevier Science Ltd, 2006)
Some properties such as hardness and fracture toughness of boride formed on the 99.97 wt% pure iron were investigated. Boronizing was carried out in a solid medium, consisting of Ekabor powders of 5% B4C as donor, 5% KBF4 as an activator and 90% SiC as diluent at 800 degrees C for 2, 4 and 8 h. The dominant phase formed on the substrate was found to be Fe2B that had a finger-like shape morphology. The hardness of boride on the 99.97% pure iron was over 1700HVN, while the hardness of pure iron was about 130HVN. It was found that the fracture toughness of boride formed on surfaces of 99.97% pure iron, depending on the process time, ranged from 3.59 to 3.83MPa m(1/2). Depending on process time and temperature, the depth of the boride layer ranges from 22 to 43 mu m, leading to a diffusion-controlled process. (c) 2006 Elsevier Ltd. All rights reserved.
5th International Symposium on Applied Plasma Science (ISAPS 05) -- SEP 26-30, 2005 -- Honolulu, HI
Keywords: boronizing; borides; pure iron; hardness; fracture toughness